Cultural spaces inside and outside caves: a study in Guam, western Micronesia. (4th April 2017) - Carson, Mike T.
Abstract: Abstract : The limestone cliff face overlooking the coastline of Ritidian, on Guam, has revealed several caves with evidence of human activities. Since 2011, archaeological survey and excavation have exposed how use of the caves had changed over time, and that they were the focus of special behaviours, with quite distinct archaeology to that of nearby residential sites. To understand the significance of these caves fully, they must be contextualised within the broader framework of contemporary open-air sites. The result highlights the use of the caves for unique purposes at different times, including as water sources, venues for various art traditions and particular burial customs.